2019
DOI: 10.1038/s41390-019-0684-1
|View full text |Cite
|
Sign up to set email alerts
|

Nephron loss detected by MRI following neonatal acute kidney injury in rabbits

Abstract: Background: Acute kidney injury affects nearly 30% of preterm neonates in the intensive care unit. We aimed to determine if nephrotoxin-induced AKI disrupted renal development assessed by imaging (CFE-MRI). Methods: Neonatal New Zealand rabbits received indomethacin and gentamicin (AKI) or saline (control) for four days followed by cationic ferritin (CF) at six weeks. Ex vivo images were acquired using a gradient echo pulse sequence on 7T MRI. Glomerular number (N glom) and apparent glomerular volume (aV glom)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…In this work, we have examined the development of vascular and glomerular pathology in a rabbit model of neonatal AKI, using 3D MRI. Although, indomethacin and gentamicin have been established as nephrotoxic in the developing kidney of the neonatal rabbit (Charlton et al, 2019), to our knowledge no studies have examined the long-term effect of the combination of these drugs on the vasculature integrated with glomerular morphology of the whole kidney. We have demonstrated that a short exposure to commonly encountered medications during an active period of nephrogenesis results in a 50% reduction of glomeruli by MRI, along with significant vascular changes, with differences in the spatial maps of the cortical vasculature and the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we have examined the development of vascular and glomerular pathology in a rabbit model of neonatal AKI, using 3D MRI. Although, indomethacin and gentamicin have been established as nephrotoxic in the developing kidney of the neonatal rabbit (Charlton et al, 2019), to our knowledge no studies have examined the long-term effect of the combination of these drugs on the vasculature integrated with glomerular morphology of the whole kidney. We have demonstrated that a short exposure to commonly encountered medications during an active period of nephrogenesis results in a 50% reduction of glomeruli by MRI, along with significant vascular changes, with differences in the spatial maps of the cortical vasculature and the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…We developed the model of renal injury in neonatal rabbits using indomethacin and gentamicin and the biochemical and histologic evaluation of this model was recently published (Charlton et al, 2019). Gentamicin and indomethacin are medications used clinically in preterm human neonates to treat deadly bacterial infections and patent ductus arteriosus, but are associated with neonatal AKI (Rhone et al, 2014).…”
Section: Animal Preparation and Labeling With Cfmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in the current setting we were not able to perform the experiment using cationic ferritin enhanced-MRI, a novel and promising tool to quantify perfused glomeruli. This method, however, would not provide insight into differences in the developmental stages of the glomeruli that were found [ 30 , 31 ]. Secondarily, kidneys were embedded in paraffin: a method known to cause 40–50% shrinkage of soft tissues such as the kidney [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 More recently, we showed that acute kidney injury in a neonatal rabbit model caused a detectable loss of glomeruli with vascular reorganization. 35 Thus, tracking changes in CF labeling by MRI may be an important tool to understand the impact of damage during development and its impact of renal health later in life.…”
Section: Ex Vivo Approaches To Measuring Nephron Number and Glomerulamentioning
confidence: 99%